2010
DOI: 10.5005/jp-journals-10013-1022
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Septoplasty: Advantages and Disadvantages

Abstract: Our study was conducted to assess the advantages and disadvantages of use of endoscopes use in septoplasty. Hundred patients with symptomatic deviated nasal septum were randomly divided into endoscopic septoplasty (ES) group and conventional septoplasty (CS) group of 50 patients each. The two groups were compared for technique, improvement in symptoms and complications. The postoperative symptoms and complications were significantly less in ES group due to better visualization and minimal dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
4
10
2
Order By: Relevance
“…In our study septal flap tear was reported to be high in conventional septoplasty and this finding was in concurrence with study done by Suligavi et al in Karnataka 4 . Endoscopic septoplasty allows limited incision and elevation of the flaps not compromising adequate exposure of the pathological site.…”
Section: Discussionsupporting
confidence: 92%
“…In our study septal flap tear was reported to be high in conventional septoplasty and this finding was in concurrence with study done by Suligavi et al in Karnataka 4 . Endoscopic septoplasty allows limited incision and elevation of the flaps not compromising adequate exposure of the pathological site.…”
Section: Discussionsupporting
confidence: 92%
“…The wealth of studies that described individual experiences with each technique, as well as the numerous studies in our review that compared clinical outcomes between the two techniques, attest to the lack of management consensus today. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] In this systematic review and meta-analysis, we set out to critically evaluate the clinical outcomes of open versus endoscopic septoplasty techniques based on the most up-to-date methodologic principles. We aimed to provide both qualitative and quantitative syntheses of the available evidence of one of the most frequently performed proce-dures in otolaryngology-head & neck surgery today.…”
Section: O N O T C O P Y Discussionmentioning
confidence: 99%
“…In another study by Sulligavi et al, the difference was significant similar to this study. 6,21 As stated earlier, conventional septoplasty employ conventional technique using head light for surgery.…”
mentioning
confidence: 99%